2016
DOI: 10.1055/s-0036-1593390
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Fixation of Metacarpal Fractures Using Headless Compression Screws

Abstract: BackgroundThere is a lack of consensus on optimal treatment methods for operative fixation of metacarpal fractures. 1 Classic treatment options include plate and screw fixation or percutaneous fixation with Kirschner wires (K-wires). 1,2 For subcapital fractures or those fractures involving the metacarpal neck, the lack of distal purchase can preclude plate and screw fixation. Short oblique, transverse, comminuted, or multiple metacarpal shaft fractures typically require more rigid fixation with lag screws or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 24 publications
(34 reference statements)
1
47
0
Order By: Relevance
“…Many studies have already attempted to prove clinical usefulness of headless compression screws in metacarpal fractures. Tobert et al16) suggested that intramedullary headless screw fixation of metacarpal fractures was an efficacious treatment modality for patients with comminution, multiple fractures, malrotation, and those who required rapid mobilization. Ruchelsman et al17) concluded that limited open retrograde intramedullary headless screw fixation was safe and reliable for metacarpal neck and subcapital and axially stable shaft fractures, allowed for early postoperative motion without affecting union rates, and obviated immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have already attempted to prove clinical usefulness of headless compression screws in metacarpal fractures. Tobert et al16) suggested that intramedullary headless screw fixation of metacarpal fractures was an efficacious treatment modality for patients with comminution, multiple fractures, malrotation, and those who required rapid mobilization. Ruchelsman et al17) concluded that limited open retrograde intramedullary headless screw fixation was safe and reliable for metacarpal neck and subcapital and axially stable shaft fractures, allowed for early postoperative motion without affecting union rates, and obviated immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to K-wire cross pinning, intramedullary fixation was shown to produce an improved range of motion and lower incidences of shortening [ 24 , 30 ]. A study retrospectively followed the outcomes with the usage of headless intramedullary screws for metacarpal neck and shaft fractures and concluded that the functional outcomes were excellent, producing a total range of motion of more than 240 degrees [ 26 ]. However, Padegimas et al support the use of headless screws for neck fractures only [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…The screw is buried into the bone, which precludes the need for subsequent removal. Tobert et al suggested that this characteristic, along with improved rotational stability of the fracture reduction, offers an advantage over other techniques, such as K-wires, which require a repeat procedure to remove the wire [ 26 ]. Since the MCP joint surface is implicated during the insertion of the screw, violation of the articular surface is a concern to bear in mind.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations